The Influence of Human Capital on Performance and Satisfaction of Medium Entrepreneurs in Kupang City - Syarifuddin Syarifuddin; Mahfudnurnajamuddin Mahfudnurnajamuddin; Ratna Dewi (Budapest International Research and Critics University, 2019)
This aims of this study is to know the influence of human capital on performance and customer satisfaction as well as medium entrepreneur human capital towards the entrepreneurs satisfaction through the performance medium entrepreneurs. This study was conducted in Kupang city with number of population 280 people as medium entrepreneurs. Sample assignment as much as 165 people medium entrepreneurs as respondents by using the method of withdrawal of samples through a formula approach Yamane. Results of the questionnaire on data analysis using Structural Equation Modeling (SEM) programmed package with the helping of Moment Analysis of Structure (AMOS) 18. The study found that; 1) Humana capital positive and significant effect on performance, medium-2) entrepreneur Human capital effect positive use and significantly to the satisfaction of the medium entrepreneurs, 3) positive use of influential businessmen and Performance significantly to satisfaction medium, 4) entrepreneur Human capital effect positive and significantly to the satisfaction of the employers through the performance medium entrepreneurs.